Some biochemical parameters in sheep infested with cocnurus cerebralis and oestrus ovis - Nurcan Dönmez; Ercan Keskin (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine the changes in some antioxidants and biochemicals of sheep infested with C. cerebralis and O. ovis. In the study, 10 sheep as control, 10 sheep infested with C.cerebralis and 10 sheep infested with O.ovis were used. In blood samples takon Irom all groups, MDA, GSH, ALT, AST, total protein, cholesterol, glucose, albumine, triglyceride levels were determined. There is no difference between groups in respect of MDA, GSH, ALT, AST levels and other biochemicals cxpect of higher glucose level (p<0.05) in C.cerebralis group. As a result, the data presented in the study will be beneficial for diagnostic and therapeutic approaches related this issue.